2018
DOI: 10.1002/ejic.201701079
|View full text |Cite
|
Sign up to set email alerts
|

A Two‐Dimensional Metal–Organic Framework as a Fluorescent Probe for Ascorbic Acid Sensing

Abstract: Ascorbic acid (AA) is an important biological molecule, but the detection of AA is still a huge challenge. Therefore, highly sensitive and selective fluorescent sensors for AA determination are urgently demanded. In this work, the new organic linker 4,4′-(1H-pyrazole-1,3-diyl)dibenzoic acid (H 2 L) was prepared to construct the new two-dimensional metalorganic framework (MOF) ZnL(H 2 O) (ZJU-137, ZJU = Zhejiang [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 64 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…These results implied that HNU‐31 was a good luminescent sensor for the quantitative analysis of Al 3+ ion. In addition, the detection limit was 4.4 × 10 −6 M calculated with 3 σ/k ( k : slope, σ : standard) . The detection limit is comparable to some reported MOFs for Al 3+ ion detection …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These results implied that HNU‐31 was a good luminescent sensor for the quantitative analysis of Al 3+ ion. In addition, the detection limit was 4.4 × 10 −6 M calculated with 3 σ/k ( k : slope, σ : standard) . The detection limit is comparable to some reported MOFs for Al 3+ ion detection …”
Section: Resultssupporting
confidence: 77%
“…Compared to the free ligand located at 415 nm (Figure S4), the emission peak of HNU‐31 was blue‐shifted with 13 nm. The differences might be related to the ligand‐to‐metal charge transfer (LMCT) …”
Section: Resultsmentioning
confidence: 99%
“… , Despite the wide range of applications of this class of materials in chemiresistive sensing of gases, ion-to-electron transduction in potentiometry, energy storage, catalysis, and electrochemically driven reversible gas capture, the use of conductive MOFs as active components in voltammetric detection of multianalyte systems has been limited . To this day, MOFs have been primarily used as colorimetric and luminescence sensors, scaffolds, and carriers , in biosensors rather than the electroactive materials due to limited conductivity and stability in aqueous solutions . Recently, the ability to achieve conductivity in 3D MOFs, through doping or mixing with conductive materials such as carbon or metal nanoparticles, has enabled the implementation of these composite materials in the detection of glucose, l -cystine, and dopamine .…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, by introducing the Eu ions into the MOFs ZJU-136-Ce, the Qian group constructed a dual-emissive MOFs, ZJU-136-Ce 1−x Eu x (x = 0.24, 0.36), which can serve as an efficient ratiometric probe for monitoring AA [122]. The same research group also reported a new Zn-MOF, ZnL(H 2 O) (ZJU-137, H 2 L = 4,4′-(1H-pyrazole-1,3-diyl)dibenzoic acid, for the fluorescence “turn-off” detection of AA [123].…”
Section: Mof-based Chemodosimeters For Other Redox-active Biomolecmentioning
confidence: 99%